Sport mega-events: can legacies and development be equitable and sustainable? - Jay Coakley; Doralice Lange Souza (Universidade Estadual Paulista (UNESP), 2013)
Sport mega-events (SMEs) involve struggles to determine the definition of legacy and the outcome priorities that guide legacy planning, funding, and implementation processes. History shows that legacies reflect the interests of capital, and legacy benefits are enjoyed primarily, if not exclusively, by powerful business interests, a few political leaders, and organizations that govern high performance sports. This paper addresses challenges faced by cities and countries that host SMEs, and shows that fair and equitable legacies and developmental outcomes are achieved only when the voices and interests of the general population are taken into account and given priority during the process of planning, funding and implementation. It also explains how full representation in the process of defining and achieving legacies and developmental outcomes may be undermined by populist beliefs about the power of sport.